The Potsdam Open Source Radio Interferometry Tool (PORT). (19th October 2021) - Schuh, H.; Heinkelmann, R.; Beyerle, G.; Anderson, J. M.; Balidakis, K.; Belda, S.; Dhar, S.; Glaser, S.; Jenie, O. S.; Karbon, M.; Kitpracha, C.; Küreç Nehbit, P.; et al.
Abstract: The Potsdam Open Source Radio Interferometry Tool (PORT) is the very long baseline interferometry (VLBI) analysis software developed and maintained at the GFZ German Research Centre for Geosciences. Chiefly, PORT is tasked with the timely processing of VLBI sessions and post-processing activities supporting the generation of celestial and terrestrial reference frames. In addition, it serves as a framework for research and development within the GFZ's VLBI working group and is part of the tool set employed in educating young researchers. Starting out from VLBI group delays, PORT estimates station and radio sources positions, as well as Earth orientation parameters, tropospheric parameters, and station clock offsets and drifts. The estimation procedures take into account all the necessary data analysis models that were agreed on for contributing to the ITRF2020 processing activities. The PORT code base is implemented in the MATLAB ® and Python programming languages. It is licensed under the terms of the GNU General Public License and available for download at GFZ's Git server https://git.gfz-potsdam.de/vlbi-data-analysis/port .